Experimental Evaluation of the Tribological Properties of Rigid Gas-Permeable Contact Lens Under Different Lubricants - Chen-Ying Su; Hsu-Wei Fang; Mousa Nimatallah; Zain Qatmera; Haytam Kasem (Lubricants)
Myopia patients wear rigid gas-permeable contact lenses during the day to achieve normal vision, but they might feel uncomfortable, since they are made of hard materials that can cause inappropriate friction and adhesion. These forces affect the biological tissues of the cornea and eyelid. In this study, an in vitro rigid gas-permeable contact lens friction testing method was established to mimic the friction between the eyelid and the rigid contact lens. The lens was rubbed against a gelatin membrane to investigate the tribological properties of artificial tear, saline, and two kinds of care solutions using a dedicated experimental setup. The viscosity, pH value, and surface tension of each lubricant was also analyzed. The friction coefficient of the artificial tear solution was the highest: 0.18 for its static friction and 0.09 for its dynamic friction. In contrast, polysaccharide-containing care solution demonstrated the lowest friction coefficient. The viscosity of artificial tear solutions ranged from 0.97 ± 00 to 1.15 ± 0.16 mPa·s, when the shear rate was increased from 19.2 to 192 1/s, while it ranged from 2.26 ± 1.12 to 2.91 ± 0.00 for polysaccharide-containing care solution. Although the physical–chemical properties of various lubricants could not explain the distinct tribological outcomes, the in vitro tribological testing method for rigid gas-permeable lenses was successfully established in this study.